O jogo das ruas: movimento de atletas contra o racismo - Florenzano, Gianluca (2023)
May 25, 2020. The United States boils over. Protest, whether black or white, men, women and children take over the country. The revolt of the Americans quickly spread to the planet. The world, which at that point was paralyzed due the COVID-19 pandemic, saw people leaving their homes, facing the contagion of the virus with an open heart and walking to the streets. The reason for the protest: the brutal murder of another African-American man by the hands of the police. For the authorities, what was supposed to be just another case of just another black person killed, for many, was enough. The lifeless body of George Perry Floyd Jr. in the middle of the street and in broad daylight became the symbol of a revolution. A global anti-racist uprising emerged. Sport, one of the main social mobilization tools, could not be left out of this fight. With the streets screaming for the end of racism, athletes, at least those in the progress field, began to get involved with the cause. However, they didn’t restrict themselves to protocol posts on social medias. On the contrary, the athletes fight with body and soul for the black cause. More than marching side by side with the people, in the US, many of them created and promoted campaigns to combat racism that impacted fans, the advertising business and even the results of the 2020 presidential election. The American athletes campaigns inspired athletes of most modalities and nationalities. More than never, the anti-racism flag emerged within the sport. In other words, on courts and arenas around the world, including Brazil, a movement of the athletes against racism was taking shape. Therefore, the objective of this research is to analyze the George Floyd case and the protest that happened in the US and other regions. In addition, we will study the campaigns promoted by the athletes and the movement against racism that emerged within sport. Also, we will talk about Brazil, analyzing the Brazilian politico and social context, and how the Brazilan players faced the anti-racism uprising that was emerging across the globe